2013
DOI: 10.1002/hep.26245
|View full text |Cite
|
Sign up to set email alerts
|

Association of tattooing and hepatitis C virus infection: A multicenter case-control study

Abstract: Although injection drug use (IDU) and blood transfusions prior to 1992 are well-accepted risk factors for hepatitis C virus (HCV) infection, many studies that evaluated tattooing as a risk factor for HCV infection did not control for a history of IDU or transfusion prior to 1992. In this large, multicenter, case-control study, we analyzed demographic and HCV risk factor exposure history data from 3,871 patients, including 1,930 with chronic HCV infection (HCV RNA-positive) and 1,941 HCV-negative (HCV antibody-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
40
0
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(55 citation statements)
references
References 42 publications
8
40
0
7
Order By: Relevance
“…Similar ndings were reported in Central Africa (29), Brazil (10) and Jordan (30). Unexpectedly, however, factors such as intravenous drug usage and tattooing did not signi cantly associate with HCV infection in north-eastern Croatia, contrary to data from other studies (31)(32)(33). Whether this is due to the small number of participants in our study remains to be elucidated.…”
Section: Discussionsupporting
confidence: 66%
“…Similar ndings were reported in Central Africa (29), Brazil (10) and Jordan (30). Unexpectedly, however, factors such as intravenous drug usage and tattooing did not signi cantly associate with HCV infection in north-eastern Croatia, contrary to data from other studies (31)(32)(33). Whether this is due to the small number of participants in our study remains to be elucidated.…”
Section: Discussionsupporting
confidence: 66%
“…[32][33][34][35] Like other studies, 5,6,23,24,28,36 our results also showed no statistically significant association between possible occupational risk factors for HBV infection among beauticians. However, some studies have suggested that beauticians are a high-risk group for HBV and HCV infections based on the statistically significant difference in prevalence among case and control groups, 24,36,37 or by comparing HBV infected cases with HAV infected cases as a control group. 6 A systematic review and meta-analysis found that tattooing was a risk factor for HCV transmission in particular, but only in a non-professional setting.…”
Section: Discussionsupporting
confidence: 73%
“…Several studies reported that beauty treatment activities, especially shaving and tattooing, might be associated with HBV and HCV infections. [5][6][7][23][24][25] Our study demonstrated that the prevalence of HBV infection among beauticians in Quy Nhon City, Binh Dinh province was 7.3% (95% CI: 4.4-11.3). This result was similar to the reported global HBV prevalence, indicating that Viet Nam was classified as a region of high-intermediate level of HBV infection (5-8%).…”
Section: Discussionmentioning
confidence: 76%
“…For example, we did not investigate the economic benefit of screening high-risk groups such as immigrants from high-burden countries, emergency department or in-hospital populations, skin-piercing practitioners or low-income groups. Recent studies in the US have shown that populations such as patients undergoing hemodialysis, 70 health care professionals, 71,72 skin-piercing practition ers 73 and low-income groups 74 have contributed substantially to the overall prevalence of chronic HCV infection in that country. Screening for chronic HCV infection within these high-risk groups in Canada could be explored as an alternative strategy.…”
Section: Limitationsmentioning
confidence: 99%